2013
DOI: 10.4028/www.scientific.net/amm.446-447.823
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of Dye Sensitized Solar Cell by Using Recycle Material for Counter Electrode

Abstract: This project is to investigate the counter electrode material from two different carbon sources to fabricate dye sensitized solar cell (DSSC). The carbon sources are extracted from battery and pencil lead. The method to prepare the DSSC is through the conventional Dr.Blading method. The same method is also used for the counter electrode which uses carbon from recycle batteries, the carbon from pencil lead are scribbled onto the ITO glass to get a uniform coating. Both thickness of the counter electrode vary ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Nair et al compared two carbon sources for the counter electrode, pencil lead and recycled carbon from batteries. They concluded that the DSSC counter electrode with carbon from recycled batteries has a higher efficiency than cells with pencil lead [35]. Both options could improve the residual material stream for batteries or nearly spent pencils.…”
Section: Using Recycled Materials To Build Dsscsmentioning
confidence: 99%
“…Nair et al compared two carbon sources for the counter electrode, pencil lead and recycled carbon from batteries. They concluded that the DSSC counter electrode with carbon from recycled batteries has a higher efficiency than cells with pencil lead [35]. Both options could improve the residual material stream for batteries or nearly spent pencils.…”
Section: Using Recycled Materials To Build Dsscsmentioning
confidence: 99%